Writing for Old and New Media: A Natural Experiment - Bode, Leticia (AoIR Selected Papers of Internet Research, 2013)
This project seeks to consider how different constraints in online versus print journalism encourage differences in political journalistic content. A natural experiment furthers our understanding of this phenomenon by holding other aspects (namely, the journalist) constant. A sample of reporters who changed jobs from online to print, print to online, as well as control groups of those switching online to online and print to print, are considered and compared in terms of content topic, length, language, frequency, and other dimensions. The implications of these differences for news audiences, as well as society at large, are discussed.